Persepsi Guru, Orang Tua dan Siswa Tentang Kecacingan di SD Smart School Swari Kabupaten Deli Serdang - Sumanto Napitupulu, David; Agree Kartini Sihombing, Ruth; Rayani Bangun, Seri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
with lower middle-class economic status and limited sanitation environments. The effects of worms can disrupt the digestive system to serious complications that affect other organs of the body. A toddler in Jember complained of difficulty defecating, stomach ache, nausea and shortness of breath and underwent surgery and 3 jars of worms were removed from the toddler's body. This case is a real example of how worms are very dangerous for children in particular. Teachers act as the best educators for students at school, parents act as the best reminders for children at home and students act directly as patients in worm infestation. Worm infections are often found in society, but it is still necessary to find the right solution to reduce the number of worm infections. The purpose of this study was to explore the perceptions of teachers, parents and students about worms at Smart School Swari Elementary School, Deli Serdang Regency. The research design is qualitative phenomenology with research instruments in the form of informant language through direct interviews conducted. The results of the interview showed that the perception of teachers, parents and students regarding worms is a disease caused by parasitic worms and attacks the human digestive tract. The factors that cause worms are unhealthy lifestyles and uncleanliness of oneself and the surrounding environment. The impact of worms can cause digestive problems, itching in the anus, loss of appetite, weight loss, inability to focus on studying, lack of enthusiasm for studying, anemia. Prevention of worms can be done by taking worm medicine, maintaining personal and environmental hygiene, consuming perfectly cooked food, consuming garlic, moringa leaves, guava leaves and Chinese stink beans. perception, worms, SD Smart School Swari, teachers, students, parents.